2021
DOI: 10.3390/s21093103
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Urban Navigation Systems for Visually Impaired People

Abstract: Blind and Visually impaired people (BVIP) face a range of practical difficulties when undertaking outdoor journeys as pedestrians. Over the past decade, a variety of assistive devices have been researched and developed to help BVIP navigate more safely and independently. In addition, research in overlapping domains are addressing the problem of automatic environment interpretation using computer vision and machine learning, particularly deep learning, approaches. Our aim in this article is to present a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 153 publications
(250 reference statements)
0
18
0
Order By: Relevance
“…These are described and evaluated in the paper, on the basis of performance features concerning capturing device, feedback, coverage area, weight, and cost. A systematic review of outdoor pedestrian navigation systems for visually impaired people reported in literature from 2015 to 2020 is presented in [49]; even though the system analysis is very accurate leading to an interesting hierarchical taxonomy, the scope of this review is limited to one type of users moving in urban environments only. A systematic review of solutions for blind and visuallyimpaired people is presented in [87]: 191 most relevant articles published between 2011 and 2020 have been selected from different digital libraries and analyzed according to different dimensions, such as approaches and technologies proposed for navigation, hardware components used for obstacle avoidance, and adopted performance metrics.…”
Section: Related Workmentioning
confidence: 99%
“…These are described and evaluated in the paper, on the basis of performance features concerning capturing device, feedback, coverage area, weight, and cost. A systematic review of outdoor pedestrian navigation systems for visually impaired people reported in literature from 2015 to 2020 is presented in [49]; even though the system analysis is very accurate leading to an interesting hierarchical taxonomy, the scope of this review is limited to one type of users moving in urban environments only. A systematic review of solutions for blind and visuallyimpaired people is presented in [87]: 191 most relevant articles published between 2011 and 2020 have been selected from different digital libraries and analyzed according to different dimensions, such as approaches and technologies proposed for navigation, hardware components used for obstacle avoidance, and adopted performance metrics.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, 5G networks can reduce roundtrip latency to 1 ms [42]. Visually impaired applications with strict latency requirements, such as navigation systems [43], can benefit significantly. The same applies to sound recognition systems for the hearing impaired, designed to prevent accidents or alert about emergencies (e.g., fire alarm, car horn).…”
Section: Low Latencymentioning
confidence: 99%
“…Accordingly, Gamal et al in [19] presented an assistance system for visually impaired people when navigating in unknown outdoor spaces, they used a deep-learning method to give the user independent mobility. Taher et al [24] presented a systematic analysis of the recently developed systems for urban navigation of visually impaired people. For his part, Babar et al [25] presented a teleguidance-based navigation assistance system for the blind and the visually impaired.…”
Section: Related Workmentioning
confidence: 99%